FACTORS FOR IMPROVING THE ACTIVITIES OF LOCAL REPRESENTATION AND EXECUTIVE BODIES IN ENSURING EFFECTIVE IMPLEMENTATION OF LOCAL BUDGETS - Mamayusupova Shokhina Ulugbek kizi (PT ANTIS International Publisher, 2024)
This article presents the ways of effective management of the local budget and the factors of further improvement of the activities of local representative and business bodies in ensuring their implementation. Also, there is information that it is possible to achieve further stabilization of the state budget by improving the local budget, and in the process of their implementation, the activities of local bodies and business bodies are also important.